Hubungan antara Hardiness dan Kesejahteraan Psikologis pada Calon Bintara Korps Wanita Angkatan Darat (KOWAD) di Pusat Pendidikan KOWAD Bandung - Roselli Kezia Ausie; Ria Wardani; Selly Selly (Universitas Kristen Maranatha, 2017)
The study aims to determine the relationship between hardiness and psychological well-being, in Bintara candidate’s of Korps Wanita Angkatan Darat (KOWAD) at Pusat Pendidikan KOWAD (Pusdikkowad) Bandung. Pusdikowad conducts educational activities with very strict routines and high discipline. For the education period 2016-2017, followed by 96 participants. Basically, the ability of respondents to persevere with the strength and courage to face this kind of pressing situation will be reflected through commitment, control, and feelings of challenge. The outcome of this hardy personality is the waking of psychological well-being. The two main concepts underlying this research are the hardiness theory of Maddi and Khoshaba (2005) and psychological wellbeing theory of Ryff (1989). The validity of hardiness instrument are between 0.34 - 0.72 with reliability of 0.821, while the validity of the psychological welfare are 0,30 - 0.70 with reliability 0.82. Research with correlation Spearman correlation method by SPSS 24.0 for Windows. The results of statistical tests show the correlation coefficient between hardiness and psychological welfare of 0.755 with significance level 0.00. Results illustrate taht any addition of hardiness strength it will be improve the psychological well-being of respondents.The proposed suggestion is to conduct a similar research but using pre and post-test design in order to get an idea of the hardiness and psychological wellbeing before and after education is implemented.